Pharmacognostical study on Piper betle L. and Ficus deltoidea Jack - Mohd Hassan, Norazian; Ahmed, Qamar Uddin; Ahmad, Kausar (2011)
This study involved the pharmacognostical evaluation of sirih melayu (Piper beetle L.) and a variety of mas cotek (Ficus deltoidea var. kuntsleri (King) Corner. The pharmacognostical approaches used include macroscopical and microscopical examination of the herbs. A method combining thin layer chromatography (TLC) analysis and bioautographic assay was employed to obtain both chemical and bioactivity profiles of the herbs, called the bioautographic profile. This study is aimed at validating the authenticity of the crude herbal drugs and quality control of the herbal preparations based on their macroscopical and microscopical characters as well as their antioxidant and antimicrobial fingerprints.